Nota su gestualità e narrazione in Matteo Bandello - Elisabetta Menetti (Laboratoire Italien)
A brief note on Matteo Bandello’s ability to describe the movements of the characters on the stage through the analysis of short stories that express the body language in communication between the characters: the novella I, 35 which deals with the gestures of a preacher and the novellas of Giulietta (II, 9: Giulietta e Romeo) and Giulia (I, 8: Giulia da Gazuolo), in which the writer describes the two women’s way of dancing and the gestures of the embrace, whether loving or violent, of their partners.